2001
DOI: 10.1080/09540120020027323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight loss on body image in HIV-positive gay men

Abstract: The purpose of this study was to assess how body image may be affected by HIV-related weight loss. Qualitative methodology was used: eight gay men with weight loss of at least 10% self-completed a brief, tailor-made questionnaire and then participated singly in semi-structured audiotaped interviews. Questionnaire analysis showed all but one had avoided social activities in the last two months due to self-consciousness over their emaciated appearance; family visits, meeting new people and meeting up again with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 0 publications
1
37
0
1
Order By: Relevance
“…According to HIV/AIDS patients research, HAART used from progression to AIDS have a significant negative impact on individuals' body image, quality of life, and mood [17] HAART, which can include fat accumulation in the abdomen, breasts, and dorso-cervical region as well as localized fat loss in the face, buttocks, and extremities [18,19].…”
Section: Definitions Of Body Image In the Literaturementioning
confidence: 99%
“…According to HIV/AIDS patients research, HAART used from progression to AIDS have a significant negative impact on individuals' body image, quality of life, and mood [17] HAART, which can include fat accumulation in the abdomen, breasts, and dorso-cervical region as well as localized fat loss in the face, buttocks, and extremities [18,19].…”
Section: Definitions Of Body Image In the Literaturementioning
confidence: 99%
“…The "contamination" of body image currently associated with lipodystrophy has been documented; however, the mechanisms underlying the visible disfiguring and stigmatizing morphological changes are still unknown (10,15,17) . In addition, BLANCH and colleagues (9) found that decreased sexual enjoyment and activity were observed after the development of lipodystrophy; however, there were no change in the frequency of condom use.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, taking into consideration the benefits of antiretroviral therapy, several patients feel that the iatrogenic costs are so difficult to tolerate that they end up by abandoning treatment (17) . This behavior can be understood if we consider not only the stigmatization currently associated with HIV/AIDS, but also the pressure for a "perfect body" currently emphasized by society.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na pesquisa de Sanches (147) , foi encontrada, em 62,50% dos indivíduos de sua amostra, perda de tecido adiposo na face, o que, segundo os pacientes, lhes conferia aspecto de envelhecimento precoce. De acordo com Tate e George (148) , dentre os segmentos corporais afetados, a lipoatrofia em face é referida como um importante fator estigmatizante para os portadores do HIV, pois os deixa mais vulneráveis na identificação da sua soropositividade e, consequentemente, na degradação de sua autoestima e socialização.…”
Section: Perfil Dos Portadores Do Hiv Segundo Lipodistrofia Autorrefeunclassified